PREVALENCE OF EIMERIA SPECIES OF LAMBS IN BAGHDAD AREA (IRAQ) - Y. Yakob, A.; M.A. Latif, B.; S.Al-Janabi, A.; I. Zaki, M. (The Iraqi Journal of Veterinary Medicine, 1989)
Four hundred and two faecal samples from lambs up to four months pld from the center of Baghdad area, were examined for the presence of coccidia parasites. The highest rate of infection (83.8) occurred in lambs about 3-8 weeks of age. Nine species of Eimeria were recovered for the first time in Baghdad namely; E. ovinoidalis, E.crandallis, E. parva, E. ninakolykimovae, E. ahsata E. Faurie, E. pallida, E. granulosa, and E. intricata. E. ovinoidalis and E. crandalli occured most frequently and were generally most predominent, the percentage of these species recorded during December were 34.7% and 21.7% respectively.